Improving mass atrocities prevention: Guidelines for effective and legitimate implementation of the responsibility to protect - Lars Brozus (Stiftung Wissenschaft und Politik (SWP), 2012)
The international community is divided over the proper interpretation and implementation of the responsibility to protect (R2P). This division contributes to the lack of collective action with respect to the situation in Syria, where mass atrocities are being committed regularly. In order to build a consensus about an appropriate prevention strategy, the concerns that were raised by some states about the illegitimate use of R2P in the case of Libya have to be addressed. These concerns focus on issues such as (1) the relation between R2P and regime change, (2) the need for enhanced accountability of the mandate-taker towards the mandate-giver and (3) the role of regional organisations. Improving the legitimacy and effectiveness of mass atrocities prevention requires a clear, consistent and convincing set of guidelines. These guidelines should be jointly developed with emerging democracies such as Brazil, India and South Africa
Keywords: 320